MIXED FINITE ELEMENT FOR THE DYNAMIC ANALYSIS OF ORTHOTROPIC FLEXIBLE SHALLOW SHELLS - Stupishin, Leonid Yulianovich; Nikitin, Konstantin Evgenyevich (Journal of Applied Engineering Science, 2017)
A finite-element methodology for studying the forced oscillations of orthotropic flexible shallow shells relative to the initial deformed state defined on the basis of a geometrically nonlinear deformation theory is proposed. To derive the finite-element equations, the Galerkin method is used in combination with the mixed formulation of the problem. The final finite-element equations have a simple structure and numerical integration is not required for calculating the matrices and vectors of finite elements. The accuracy and convergence of the mixed finite element is analyzed. Based on the developed methodology, the influence of geometric nonlinearity on the process of shell oscillations is studied.